A Compact Negative Group Delay Microstrip Diplexer with Low Losses for 5G Applications: Design and Analysis - Nouri, Leila; Yahya, Salah I.; Rezaei, Abbas; Hazzazi , Fawwaz A.; Nhu, Binh N. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
Microstrip Diplexers play an important role in modern wireless communication systems. In this paper, a novel compact microstrip diplexer based on spiral cells is presented. The proposed resonator primarily consists of two spiral thin lines connected to a pair of coupled lines. This novel resonator is analyzed mathematically to find its behavior and tune the dimensions of the final layout easily. Using the analyzed resonator, two bandpass filters (BPFs) are designed. Then, a novel high-performance microstrip diplexer is obtained by designing and integrating these two BPFs. The center frequencies of the first and second channels of the proposed diplexer are 1.86 GHz and 4.62 GHz, respectively. The proposed diplexer boasts a remarkably small size of 0.004 λg2 and features flat channels with low insertion losses of only 0.048 dB and 0.065 dB for the first and second channels, respectively. The maximum group delays of S21 and S31 are 0.31 ns, 0.86 ns, respectively, which are good values for a modern communication system. Meanwhile, inside its passbands for some frequency ranges, its group delays are negative. Thus, using this diplexer can decrease the signal dispersion. The 1st and 2nd passbands are wide with 47.3% and 47.1% fractional bandwidths (FBW), respectively. Therefore, this diplexer can be easily and successfully used in designing high-performance RF communication systems.